STRATEGI PENGEMBANGAN OBJEK WISATA DANAU RAJA KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Igawin Minarti; Syafri Anwar (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
Abstract This study aims to describe: (1) internal factors in the tourism object of in the Lake Raja in influencing tourist visits (2) external factors in the object of Raja Lake tourism in influencing tourist visits (3) The appropriate development strategy to be applied in influencing tourist visits . This type of research is a qualitative approach. Data collection techniques with observation, interviews, and documentation. The data analysis technique used is the SWOT analysis. The results showed (1) the main internal factors in terms of strengths: the uniqueness and beauty of Raja Lake which is the main attraction, in terms of weaknesses: lack of maintenance and supervision of facilities and assets. (2) the main external factor in terms of opportunities: an increase in people's economic income, in terms of threats: questionable security. (3) The right strategy for the development of the Raja Lake tourism object is (a) optimizing the resources owned, (b) carrying out maintenance and supervision (c) increasing promotional activities by utilizing technology. (d) constructing insufficient facilities and infrastructure for the convenience of visitors